A Shock to the System: What the COVID-19 Pandemic Reveals About Australia's Food Systems and Their Resilience - Jones, Natalie A.; Bellamy, Jennifer; Bellotti, William; Ross, Helen; van Bommel, Severine; Liu, Yiyu (Frontiers in Sustainable Food Systems, 2022)
Australia has managed well through the COVID-19 pandemic, compared to many other developed nations. Through its first and second waves it was relatively successful in terms of control of outbreaks. Nevertheless, like everywhere, the shock to national systems has been profound, and adjustment remains complex and volatile. Food is a critical human need, and the food industry is recognised as a vital economic sector. We present an examination of some of the adaptive responses of Australia's food systems during the early stages of the COVID-19 pandemic, from January 2020 to October 2020, with a focus on three case studies (seafood exports, consumer behaviour and food sector employment). These case studies provide observations of specific stresses experienced, as well as insights into the adaptation strategies carried out by various actors within the nation's food systems. The shock was experienced differently in different parts of given food systems, and the opportunities for adaptation varied. Some supply chains lost business, others had to adapt to rapidly increased demands, and surges. Our analysis reveals features of Australia's food systems, and their relationships to other systems, that have facilitated resilience, and features that have impeded it. We found that international supply chains are highly vulnerable to global shocks, that insecure employment conditions throughout the food system reduce the resilience of the system overall, and that consumers are not fully confident in supply chains. We observed the importance of agency and adaptive behaviour throughout the food systems as actors worked to build their own resilience, with consequences for other parts of the system. Our findings suggest that food system resilience can be enhanced by ensuring that the goals and priorities of those most vulnerable in society are recognised and addressed within decision making processes throughout the system.